AKUNTABILITAS PENGELOLAAN DANA DESA DI DESA KALINUSU KECAMATAN BUMIAYU KABUPATEN BREBES TAHUN 2021 - Tohir; Sutikno, Chamid; Ariesta Amanda (Economics, Social, and Humanities Journal (Esochum), 2024)
The importance of accountability in state financial management is the main focus in the implementation of public organizations, because it can determine the continuity and gain the trust of the public. This study aims to analyze the accountability of village fund management in Kalinusu Village, Bumiayu District, Brebes Regency in 2021. Descriptive qualitative method was used to describe the accountability of village fund management. The research was conducted in Kalinusu Village, Bumiayu Subdistrict, Brebes Regency. The selection of informants was carried out using purposive sampling technique, with 15 informants selected from various elements considered to have knowledge about the management and reporting of the Village Fund. This research focused on one research focus, namely the accountability of Village Fund management in Kalinusu Village. Data were collected using observation, interviews, and documentation. The collected data were analyzed using descriptive qualitative research methods with interactive techniques. To ensure the validity of the research data, data triangulation techniques were used. The results showed that the Kalinusu Village Government has successfully applied the principles of accountability, namely transparency, accountability, control, responsibility, and responsiveness in the management of the Village Fund. Overall, the Kalinusu Village government has demonstrated high responsibility in managing the Village Fund, has met competency standards, complied with regulations, and acted transparently and accountably. Thus, community trust in the village government increases, and the gap between the community and the government can be bridged.